INVENTARISASI SERANGGA TANAH DI TAMAN WISATA ALAM GUNUNG TUNAK KABUPATEN LOMBOK TENGAH - Uswatun Hasanah; Nofisulastri Nofisulastri; Safnowandi Safnowandi (Bioscientist : Jurnal Ilmiah Biologi, 2020)
Gunung Tunak Nature Tourism Park is a nature conservation area which is mainly used for tourism and nature recreation. Gunung Tunak Nature Tourism Park is one of 17 conservation areas managed by the Natural Resources Conservation Center (BKSDA), located in Mertak Village, Pujut District, Central Lombok Regency. Geographically located between 08º53'30.08º57'30 South Latitude, and 116º24'00” East Longitude. The purpose of this study was to determine the types of soil insects found in the Gunung Tunak Nature Park. This type of research is exploratory descriptive. The sampling method uses pitfall traps. Sampling locations include the park area in front of the butterfly breeding, and in front of the camping ground as posts 1 and 2. Sampling was carried out in the morning (07.00-09.30 WITA), and in the afternoon (16.00-17.30 WITA) with 3 repetitions. Soil insect samples obtained were identified at the level of the order and family at the Biology Laboratory, Mandalika University of Education. The results showed that 6 soil orders were found, namely: Orthoptera, Hymenoptera, Hemiptera, Diptera, Coleoptera, and Scorviones. The highest group of individuals found was the Hymenoptera Order with 93 individuals.